The Effects of Agglomeration and National Property Rights on Digital Confidentiality Performance. Issue 1 (26th September 2016) - Massimino, Brett; Gray, John V.; Boyer, Kenneth K.
Abstract : In recent years, instances of organizations failing to maintain digital confidentiality performance have greatly increased in frequency and monetary damage. While the global sourcing of activities in the development of digital assets is widespread, very little is known about how location‐related factors may affect confidentiality outcomes. Addressing this, we empirically investigate two factors with rich theoretical bases and logical linkages to confidentiality: industrial agglomeration and national property rights protections. We conduct a large‐scale, empirical study at the product level of analysis, and treat the confidentiality of a digital product as a performance outcome that is affected by the locations of the two key organizational entities involved in the product's development. We leverage modern, web‐crawling methods to harvest secondary data from a major, illicit distribution channel for these products and combine these data with other secondary data involving legitimate commerce to derive a secondary measure of confidentiality performance. We find robust results, and demonstrate practical significance of our findings through scenario analyses based on actual data from our sample.